CUTANEOUS STREPTOCOCCAL ABSCESS TREATED BY PHOTODYNAMIC THERAPY - Sellera, Fábio Parra; Barbosa, Bruna Stanigher; Gargano, Ronaldo Gomes; Sabino, Caetano Padial; Simões, Martha Ribeiro; Azedo, Milton Ricardo; Benesi, Fernando José; Pogliani, Fabio Celidonio (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Photodynamic therapy has been investigated in different areas of health through experimental conditions. Its action can alter fundamental structures for the survival of microorganisms without any development of microbial resistance. Materials and Methods: Young sheep presenting with abscess in the left forelimb caused by Streptococcus spp. was previously treated with antibiotics. There was no clinical improvement with the treatments, and the bacteria presented sensitivity in vitro. Therefore, Photodynamic therapy associating methylene blue and red laser (660 nm) was used to treat the abscess. Results: After a day of treatment, complete healing was witnessed with no recurrence was observed during the 3-month follow-up period. Conclusion: The scientific results of the antimicrobial effect of PDT proved to be a therapeutic option with great potential for clinical application.